P. micra and F. necrophorum: Hepatic Abscesses in a Healthy Soldier. (26th March 2022) - Strobel, Samuel; Whitaker, Daniel; Choi, Edwin; Lindow, Janelle; Lago, Kathryn
Abstract : Parvimonas micra (P. micra) and Fusobacterium necrophorum (F. necrophorum) are two pathogens known to cause odontogenic and oropharyngeal infections. It is exceedingly rare for these bacteria to cause coinfection and even systemic infection. There is limited literature on liver abscesses and bacteremia involving P. micra . Most cases are found in elderly patients with associated gastrointestinal malignancy (24%) or laryngeal pharynx malignancy (28%). However, a substantial portion of described cases were unable to identify a source (36%). A 36-year-old, otherwise healthy male presented for fevers and chills for 2 weeks. After testing negative for initial infectious workup, including COVID-19 multiple times, he was found to have multiple liver abscesses which grew P. micra and F. necrophorum . This case highlights a rare coinfection of hepatic abscesses in an otherwise healthy young immunocompetent adult with a solitary dental caries, resulting in septic shock.